Digital Implementation of Doteli Dictionary: A Tri-Lingual Dictionary for Doteli Language - Bhatt, Hari Sharan (Scholars’ Journal, 2023)
This research article discusses the development and implementation of a digital Doteli dictionary, designed to bridge the linguistic gap between Doteli, Nepali, and English. The trilingual dictionary app operates on Android platforms and offers functionalities such as word meaning searches, antonym/synonym retrieval, pronunciation guides, language translation, and the ability to bookmark words. Physical dictionaries have several limitations, including bulkiness, low portability, time-consuming searches, difficulty in modification, limited accessibility, and the absence of pronunciation features. According to the literature, no digital version of the Doteli dictionary has been developed to date. This research aims to address these limitations by providing a digital version of the Doteli dictionary that includes all the aforementioned features. Drawing inspiration from traditional dictionaries, the digital version seeks to preserve, promote, and make the linguistic richness of the Doteli language more accessible. The development and testing of the app follow the System Development Life Cycle (SDLC) approach, with all sample data sourced from physical dictionaries. The system has been successfully implemented and installed on Android-based mobile devices using Java programming. This work is beneficial for language learners, linguists, researchers, teachers, students, and developers.